Estimates of on-farm antimicrobial usage in egg production in the United States, 2016–2021 - Singer, Randall S. (Frontiers in Veterinary Science, 2023)
Very few data exist globally regarding the use of antimicrobials in the table egg industry. Antimicrobial use data from broiler chickens and turkeys cannot be used as a surrogate of layer chickens because of the fact that table eggs for human consumption are produced daily by laying hens. To avoid the possibility of antimicrobial residues in the eggs, there are very few antimicrobials approved for use in layers in the U.S. The objective of this study was to collect on-farm antimicrobial use data from the U.S. table egg industry and to have it be representative of the national layer flock. Participation was voluntary. Data were collected for the period 2016 through 2021 and are reported on a calendar year basis. Using production statistics from USDA:NASS as a denominator, the data supplied by participating companies accounted for 3,016,183,140 dozen eggs (approximately 40% of national egg production) in 2016 and 3,556,743,270 dozen eggs (approximately 45% of national egg production) in 2021. All of the replacement chicks placed on pullet farms during the study period were estimated to have received 0.2 mg/chick gentamicin at the hatchery. Most of the antimicrobial administration in U.S. egg production is via the feed. The ionophores monensin and salinomycin were used in the pullets, bacitracin was used in both pullets and layers (primarily for control of necrotic enteritis), and chlortetracycline was used primarily in layers for the treatment of E. coli-related disease. In the layers, between 0.10% and 0.19% of total hen-days were exposed to chlortetracycline. Only two water-soluble administrations were recorded during the entire study period, both involving lincomycin to pullet flocks for the treatment of necrotic enteritis. Overall, antimicrobial use in the U.S. layer industry was focused mainly on controlling necrotic enteritis in the pullets and treating E. coli-related disease in the laying hens.